Rancang Bangun Software Tutorial Pengenalan Seni Tari Tradisional - Endang Setyawati (Media Aplikom, 2018)
One of the cultural heritage of ancestors that need to be preserved is Traditional dance art. Traditional Dance is a Dance art that grows and develops in a certain area and is embraced by generations by the community, one way to preserve it is by building a learning media with the title of traditional recognition of Senorari Software to preserve the culture of West Java, where this software uses the concept of AI ( Artificial Intellegence) field of education. The results of the study were conducted for 3 months, to find out how big the comparison before using the traditional dance art recognition tutorial software and after using the traditional senorari introduction tutorial software easier its learning to preserve the cultural values of the Nation. The research is done by taking the data of value and time to work on the problems before and after using the traditional dance recognition tutorial Software. Data from 50 respondents who are students majoring in dance art then researched to see the spread of the data. Then the process is incorporated into the SPSS 12.0 For Windows statistical application to be analyzed using the statistical method of PairedSamples T Test. Conclusion The results of this research is Tutorial software to facilitate the introduction of traditional dance as learning media to preserve cultural values.